Dialect variation in a cross-border language: a sociolinguistic study of Silozi in Zambia and Namibia - Mbeha, Gustav (School of African and GenderStuds, Anth and Ling, 2023)
Silozi came into existence in the early 1800s when Sikololo speakers (Makololo) from South Africa came in contact with the Siluyana speakers (Luyi) in Barotseland. Today the language is spoken by over 700 000 people in Zambia, Namibia, Botswana, Angola and Zimbabwe collectively. Of the wealth of scholarship on the Malozi and their language, most focused on development and structure. Silozi dialect variation is yet to be explored in depth. This is a study of dialect variation in cross-border Silozi. The focus is on the lexicon and the morphosyntactic structures of the Silozi varieties spoken in the towns of Katima Mulilo (Namibia) and Mongu (Zambia). As an example of mixed-methods research, the data collection was conducted using the language documentation and description approach (see Lüpke, 2010; Himmelman, 1998). The data comprised of lexicon and sample sentences elicited via structured interviews from 70 participants. In addition, metalinguistic questions were used to collect information on essential language use patterns during data analysis. The findings confirmed that Silozi is the official language in Katima Mulilo, but Chisubiya and Chifwe are the dominant lingua francas. Contrastingly, in Mongu, Silozi is the main Bantu language, with others spoken minimally. A consequence of this is that the Katima Mulilo variety contained more lexical borrowings from other Bantu languages compared to Mongu. However, both varieties borrowed more lexicon from English than from the Bantu languages. Morphosyntactically, the Katima Mulilo variety contains grammatical features from Chisubiya that are not present in the Mongu variety. Chisubiya plays a central role in the differences that emerge between the two varieties. Overall, the Mongu variety appeared to be more stable and less susceptible to change. This thesis thus illustrates that there is nuanced variation in cross-border Silozi. Language contact and migration are shown to have been significant factors in ongoing language change in cross-border dialects.